Peningkatan Hasil Belajar IPA Dengan Penerapan Pendekatan Saintifik Siswa Sekolah Dasar: Penelitian Tindakan Kelas Materi Organ Pernapasan Hewan Pada Siswa Kelas V SDN 011 Koto Tuo Kecamatan XIII Koto Kampar - Ernis Ernis; Yolanda Pahrul (Jurnal Pendidikan Tuntas, 2023)
This research is motivated by the low learning result of science at the five year students of state elementary school 011 Koto Tuo Distric of XIII Koto Kampar. One of solution to overcome this problem by implementation of scientific approach. The objective of study to know increase learning result of science material the animal's respiratory organs at the five year students of state elementary school 011 Koto Tuo Distric of XIII Koto Kampar by implementation of scientific approach. This research is a kind of Classroom Action Research (CAR) executed in two cycles. Every cycles consisted of bay one meeting and four phase, thas is planning, action, observation, and reflection. the subjects in this study is five grade students of 011 Koto Tuo Distric of XIII Koto Kampar 2017-2018 school year the number of students of 31 people, consisting of 14 men and 17 women. Data collection techniques used in this study is the observation, testing, and documentation. Having conducted research note an increase in student learning outcomes of prior actions, the first cycle and second cycle. In the pre-action mastery students only reached 45,46% or 14 students who completed, the students who pass the first cycle increased to 18 people or completeness only reached 58,06%. In the second cycle turns completeness students at 27 students or the percentage of 87,10%. Thereby that is the implementation of scientific approach to increase learning result of science material the animal's respiratory organs at the five year students of state elementary school 011 Koto Tuo Distric of XIII Koto Kampar.